Street vendors as actors of a sustainable food system—The case of Mexico City - Louise Guibrunet; Ana G. Ortega‐Avila; Selene Valerino‐Perea; José Manuel Correa Campos; Valeria Itzel Pozos Espinosa (Geo: Geography and Environment)
Abstract In this paper, we explore the role of street vendors in enhancing access to sustainable food, using Mexico City as a case study. Through observational fieldwork, we quantify and spatialize the street food offer of two municipalities, which we compare to food offer in outlets (shops and restaurants). We use Mexican traditional food as a proxy for a sustainable diet. Street vendors represent 55% of the food retailers present in the study area. Over half of street vendors only sell traditional food (against 45% of food outlets), but most sell food to be consumed in moderation (e.g. tacos). A weak statistical correlation suggests that street vendors and food outlets tend to cluster in mixed‐use areas; as such, street vendors' role in the urban food system is mainly to provide an alternative food offer in well‐served areas, rather than providing a food offer in neighbourhoods where the formal offer is scarce. We conclude that street vending is a significant element of Mexico City's urban food environment and increases the availability of traditional food, thus enhancing food sovereignty and contributing to a sustainable food system. Street vending, as an unplanned, traditional daily practice that inadvertently contributes to a sustainable food system, is an example of ‘already existing sustainabilities’, which exploration can provide crucial insights to achieve sustainability transitions.